Longitudinal viral shedding and antibody response characteristics of men with acute infection of monkeypox virus: a prospective cohort study - Yang, Yang; Niu, Shiyu; Shen, Chenguang; Yang, Liuqing; Song, Shuo; Peng, Yun; Xu, Yifan; Guo, Liping; Shen, Liang; Liao, Zhonghui; Liu, Jiexiang; Zhang, Shengjie; et al. (Nature communications, 2024)
Understanding of infection dynamics is important for public health measures against monkeypox virus (MPXV) infection. Herein, samples from multiple body sites and environmental fomites of 77 acute MPXV infections (HIV co-infection: N = 42) were collected every two to three days and used for detection of MPXV DNA, surface protein specific antibodies and neutralizing titers. Skin lesions show 100% positivity rate of MPXV DNA, followed by rectum (88.16%), saliva (83.78%) and oropharynx (78.95%). Positivity rate of oropharynx decreases rapidly after 7 days post symptom onset (d.p.o), while the rectum and saliva maintain a positivity rate similar to skin lesions. Viral dynamics are similar among skin lesions, saliva and oropharynx, with a peak at about 6 d.p.o. In contrast, viral levels in the rectum peak at the beginning of symptom onset and decrease rapidly thereafter. 52.66% of environmental fomite swabs are positive for MPXV DNA, with highest positivity rate (69.89%) from air-conditioning air outlets. High seropositivity against A29L (100%) and H3L (94.74%) are detected, while a correlation between IgG endpoint titers and neutralizing titers is only found for A29L. Most indexes are similar between HIV and Non-HIV participants, while HIV and rectitis are associated with higher viral loads in rectum. Here the authors measure viral load in samples from skin lesions, saliva, oropharynx, and rectum of 77 patients with acute monkeypox virus infection as well as from environmental fomite swabs and show a high seropositivity rate for antibodies against A29L and H3L.